Implementasi Penyusunan Laporan Keuangan Yayasan Pondok Pesantren Berdasarkan Isak 35 dan Pedoman Akuntansi Pesantren pada Yayasan Pendidikan Pondok Pesantren “Roudhotul Muttaqin” Kab. Mojokerto - Muhammad Galang S.; Tatas Ridho Nugroho; Hari Setiono; Imam Baidlowi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to find out how the preparation of the financial reports of the "Roudhotul Muttaqin" Islamic Boarding School Foundation, Mojokerto Regency and whether the preparation of the financial reports of the "Roudhotul Muttaqin" Islamic boarding school foundation is in accordance with ISAK 35 standards and Islamic boarding school accounting guidelines. This type of research is a qualitative descriptive research with a case study method that compares the financial reports of the “Roudhotul Muttaqin Islamic boarding school” with ISAK 35 standards and Islamic boarding school accounting guidelines. Data collection techniques used are documentation and interviews. The object of this research is the Islamic boarding school foundation "Roudhotul Muttaqin" Mojokerto Regency. Data analysis was carried out by comparing the components in ISAK 35 which includes a comprehensive income statement, a report on changes in net assets, a balance sheet, and a cash flow statement, while the Islamic boarding school accounting guidelines include account identification, journalism, general ledger, trial balance, and preparation of financial statements. based on ISAK 35. The results showed that the Roudhotul Muttaqin Islamic Boarding School Foundation, Mojokerto Regency had not implemented financial reports based on ISAK 35 and had not recorded the accounting cycle based on Islamic boarding school accounting guidelines.